Translators’ Allocation of Cognitive Resources in Two Translation Directions: A Study Using Eye-Tracking and Keystroke Logging - Yifang Wang; Saihong Li; Yubo Zhou Rasmussen (Applied Sciences)
This study investigates how novice translators distribute their cognitive resources during translation between English and Chinese in both directions, with particular attention paid to the role of translation direction and the divergence between empirical findings and participants’ introspective reports. A combination of eye-tracking and keystroke logging was used to quantify cognitive effort, incorporating participant variation, attention unit type (ST, TT, parallel), gaze event duration, and average pupil dilation. A Generalized Linear Model (GLM) was applied, with average pupil dilation as the response variable and gaze event duration, AU type, and participant as covariates. An interaction term between gaze event duration and AU type was included in the E-C GLM but omitted from the C-E GLM due to non-significance. The results reveal distinct cognitive demands across translation directions. In English–Chinese (E-C) translation, ST processing significantly reduces pupil dilation (by 3.56%, p < 0.001), whereas TT processing leads to increased cognitive load, particularly during prolonged fixations, with pupil dilation increasing by 1.4% (p = 0.033). In Chinese–English (C-E) translation, ST processing does not significantly differ from parallel processing (p = 0.285), and TT processing reduces pupil dilation by 4.75% (p < 0.001), suggesting that it involves a lower cognitive effort than E-C translation. Gaze event duration significantly affects pupil dilation in C-E translation (p < 0.001); however, its influence in E-C translation varies according to the types of cognitive processing involved. Moreover, a significant gap is observed between the participants’ self-reported reflections and the quantitative data, a disparity that is strongly shaped by the direction of translation. These findings contribute to a deeper understanding of cognitive effort in translation and raise implications for translator training, assessment, and cognitive translation studies, particularly in contexts where translation direction and processing mode interact to shape cognitive demand.